A Trustworthy Interoperability Architecture for Industry 4.0 - Allian, Ana Paula (2021)
Industry 4.0 has called the attention of companies by leading to highly networked smart factories and leveraging the complex manufacturing processes. The achievement of trustworthy interoperability among several heterogeneous entities and also companies is still a challenge; hence, research, standardization initiatives, and adaptation of solutions from other areas were already conducted. However, companies interested in Industry 4.0 do not have direction about what solutions or concerns/requirements should be considered to architect Industry 4.0 systems that assure trustworthy interoperability. This work contributes with a Trustworthy Interoperability Architecture (TIBA) for Industry 4.0, by combining blockchain with traditional solutions for interoperability. We firstly identified the main challenges regarding interoperability in real-world Industry 4.0 projects. Following, we designed a set of architecture drivers combining such challenges with quality aspects extracted through a systematic literature review. We refined these drivers through a survey with experts from Industry 4.0, and we defined the main architecture solution through the conduction of interviews with experts from Industry 4.0. The design of TIBA takes into account blockchain technology combined with traditional technologies used in Industry 4.0 that together cover the main concerns related to trustworthy interoperability. To evaluate TIBA, we instantiated it in a real-world scenario of Industry 4.0 and observed how a manufacturing company can automatically award contracts to incorporate capacities of outside companies into its production system. TIBA can support the design of a trustworthy interoperability solution by providing architecture drivers and architectural solutions. TIBA comprises the first set of architectural decisions regarding the combination of blockchain with traditional technologies and could contribute to realizing Industry 4.0 projects.